The hijacking of a receptor kinase-driven pathway by a wheat fungal pathogen leads to disease - Shi, G. J.; Zhang, Z. C.; Friesen, T. L.; Raats, D.; Fahima, T.; Brueggeman, R. S.; Lu, S. W.; Trick, Harold N.; Liu, Z. H.; Chao, W.; Frenkel, Z.; Xu, S. S.; et al. (My University, 2016)
Necrotrophic pathogens live and feed on dying tissue, but their interactions with plants are not well understood compared to biotrophic pathogens. The wheat Snn1 gene confers susceptibility to strains of the necrotrophic pathogen Parastagonospora nodorum that produce the SnTox1 protein. We report the positional cloning of Snn1, a member of the wall-associated kinase class of receptors, which are known to drive pathways for biotrophic pathogen resistance. Recognition of SnTox1 by Snn1 activates programmed cell death, which allows this necrotroph to gain nutrients and sporulate. These results demonstrate that necrotrophic pathogens such as P. nodorum hijack host molecular pathways that are typically involved in resistance to biotrophic pathogens, revealing the complex nature of susceptibility and resistance in necrotrophic and biotrophic pathogen interactions with plants.
Citation: Shi, G. J., Zhang, Z. C., Friesen, T. L., Raats, D., Fahima, T., Brueggeman, R. S., . . . Faris, J. D. (2016). The hijacking of a receptor kinase-driven pathway by a wheat fungal pathogen leads to disease. Science Advances, 2(10), 9. https://doi.org/10.1126/sciadv.1600822
Keywords: Pyrenophora-Tritici-Repentis; Resistance Gene; Protein; System; Toxa; Susceptibility